Are the Global Cosmetic Surgery Legal Issues Bypassing Lithuania? - Levon, Justyna; Valančienė, Dovilė (Teisė, 2021)
The article deals with an empirical study of certain legal issues of cosmetic surgery and their manifestations in legal articles abroad and in Lithuania. It examines whether the cosmetic surgery-related legal issues analysed in the authoritative databases Scopus and Clarivate analytics and the articles found therein resemble the cosmetic surgery-related legal issues analysed in authoritative Lithuanian legal journals and the Lithuanian Digital Academic Library database (eLABa) articles.
Keywords: cosmetic surgery; aesthetic surgery; plastic surgery; cosmetic surgery tourism; legal issues